Status of stem cells in diabetic nephropathy: predictive and preventive potentials. Issue 1 (December 2016) - Baban, Babak; Liu, Jun; Payne, Samuel; Abebe, Worku; Yu, Jack; Mozaffari, Mahmood
Abstract Background Recruitment of stem cells to sites of tissue injury constitutes an important mechanism aimed at tissue repair and regeneration. However, it is not clear how the diabetic milieu affects the viability of endogenous stem cells. Thus, we tested the hypothesis that diabetes mellitus is associated with increased apoptosis which, in turn, contributes to reduction in stem cells and the manifestation of type 2 diabetic nephropathy. Methods Sixteen-week-old male obese type 2 diabetic db/db mice, and their appropriate controls, were used for assessment of the status of endothelial progenitor cells (EPCs), mesenchymal stem cells (MSCs), and hematopoetic stem cells (HSCs) in the peripheral blood and renal tissue using specific cell markers. Further, we explored whether diabetic animals display greater apoptosis of stem cell subsets. Results The peripheral blood cells of db/db mice displayed reduction in EPCs (p  < 0.05) compared to those of db/m controls. Further, kidney cells prepared from experimental groups also showed reductions in EPCs, MSCs, and HSCs. We also observed increased apoptosis of stem cell subsets in cells prepared from kidneys of db/db than those of db/m mice. Conclusions The present study shows a similar pattern of decline in stem cell subsets in peripheral blood and kidneys of db/db mice, an effect likely related to increased apoptosis. Collectively, the results suggest that apoptosis of stem cells likely contributes to eventual manifestation of renal failure in diabetes mellitus. Monitoring of blood levels of stem cell subsets could predict failure of their reparative and protective effects and eventual manifestations of diabetic complications.